2008
DOI: 10.1016/j.chemphys.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the NH3–H2 van der Waals interaction by high level ab initio calculations

Abstract: The intermolecular potential energy for the van der Waals complex between ammonia and the hydrogen molecule has been studied by means of the coupled cluster CCSD(T) method and aug-cc-pVXZ (X=D,T,Q,5) basis sets and with inclusion of the Boys and Bernardi counterpoise correction. For sufficiently large basis sets the only true electronic minimum energy structure of NH3-H2 is found to possess C3v point group symmetry. Various minimum energy paths for the relative motion of NH3 and H2 are analysed in order to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…The five‐dimensional PES, including the anisotropy of H 2 , is of course qualitatively different: the global minimum, as deduced from our fit, lies at −267 cm −1 for R = 6.1 Bohrs, with H 2 co‐linear with the C 3 v axis of ammonia at the nitrogen end. It is interesting to compare this result with the recent calculations of Mladenović et al (2008): these authors found the global minimum of the NH 3 –H 2 interaction at a similar location with a comparable, although significantly smaller, binding energy (−253 cm −1 ). As their calculations were performed at a similar level of accuracy [CCSD(T) method and aug‐cc‐pVQZ basis sets], this difference most likely reflects monomer geometry effects.…”
Section: Potential Energy Surface and Collisional Ratessupporting
confidence: 68%
See 1 more Smart Citation
“…The five‐dimensional PES, including the anisotropy of H 2 , is of course qualitatively different: the global minimum, as deduced from our fit, lies at −267 cm −1 for R = 6.1 Bohrs, with H 2 co‐linear with the C 3 v axis of ammonia at the nitrogen end. It is interesting to compare this result with the recent calculations of Mladenović et al (2008): these authors found the global minimum of the NH 3 –H 2 interaction at a similar location with a comparable, although significantly smaller, binding energy (−253 cm −1 ). As their calculations were performed at a similar level of accuracy [CCSD(T) method and aug‐cc‐pVQZ basis sets], this difference most likely reflects monomer geometry effects.…”
Section: Potential Energy Surface and Collisional Ratessupporting
confidence: 68%
“…This latter was subsequently improved to investigate propensity rules at selected collisional energies for ammonia colliding with both p‐ and o‐H 2 (Offer & Flower 1990; Rist et al 1993). More recently, high‐accuracy ab initio calculations have been performed by Mladenović et al (2008) to explore the topographical features of the NH 3 –H 2 interaction. In this paper, we present new collisional rates based on the determination of a new, highly accurate, NH 3 –H 2 ab initio PES.…”
Section: Introductionmentioning
confidence: 99%
“…One may note that a similar situation was also observed in our previous study of the van der Waals complex NH 3 -H 2 . 31 From the computational point of view, this problem was resolved by combining the d-augcc-pVXZ basis for carbon, nitrogen, and oxygen with the aug-cc-pVXZ functions for hydrogen, providing a basis set denoted by d ‫ء‬ -aug-cc-pVXZ here. Since diffuse functions placed on hydrogen are expected not to participate significantly in the outer-valence region, the d ‫ء‬ -aug-cc-pVXZ set is also eligible from the physical point of view.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The H 2 monomer approaches NH 3 from the nitrogen side. This global minimum is bound by D e =253 cm −1 according to Mladenović et al (2008) and 267cm −1 according to Maret et al (2009). The potential rises steeply for other H 2 orientations, indicating hindered internal rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Not long ago, two high-accuracy ab initio five-dimensional PESs, including the anisotropy of H 2 , were obtained for the NH 3 -H 2 system using the coupled-cluster CCSD(T) method (Mladenović et al 2008;Maret et al 2009). In both studies the equilibrium structure of NH 3 -H 2 was found to be axial, with molecular hydrogen collinear with the C 3 symmetry axis of ammonia.…”
Section: Introductionmentioning
confidence: 99%